Freud's India Sigmund Freud and India's first psychoanalyst Girindrasekhar Bose - Hiltebeitel, Alf 1942-2023 (Oxford University Press, 2018)
" A theme of abiding interest in religious studies is the sharp contrast between cultures with a monotheistic paternal deity and cultures with pluralistic maternal deities. These two principles for organizing religious life are vast; attempts to understand their implications lead to an overwhelmingly diverse set of facts and their meanings. In Freud's India, Alf Hiltebeitel takes up this enormously engaging question, focusing on the thinking of two spokespeople for the inner life of their culture... Sigmund Freud and Girindrasekhar Bose. Alf Hiltebeitel considers the attempts of these two men to communicate with and understand each other and these issues, in the heated context of emotionally divisive allegiances. The book is elegant in its nuanced attention to these two thinkers, and its tightly controlled exploration of what their interactions indicate about their contributions and limitations as representatives of the psychology and religion of their respective cultures. Anxieties about mothers separate Eastern from Western imaginations. They separate Freud from Bose, and they separate Hindu foundational texts from the Hebrew foundational texts. "...